Tinjauan Penerapan Pajak Restoran Pada Rumah Makan Rumah Empangku - Khofifah Ananta Surya; Imron Burhan; Mahardian Hersanti Paramita (Politeknik Bosowa, 2021)
The existence of restaurant tax is very important as a source of regional income. Every year, restaurant tax revenue is always increased to meet the targets set by the local government. Rumah Empangku restaurant is one of the potential taxes in the Barru Regency area. Rumah Empangku Restaurant as one of the culinary destinations in Barru Regency has great potential to be developed. The purpose of this study is to determine the application of restaurant tax at Rumah Empangku restaurant and to determine the suitability of the application of restaurant tax at Rumah Empangku restaurant with regional regulations of Barru district. number 4 of 2011 on local taxes of the new district. The analytical method used is a qualitative method by collecting observation data, interviews, and documentation. The results showed that the application of restaurant tax at Rumah Empangku restaurant was in accordance with the applicable regulations, although at the beginning of the application period of the restaurant tax, Rumah Empangku was still experiencing adjustments in its application.Key word : Restaurant, restaurant tax, peraturan daera